(3ChQGO GHf YQHj (B"(3ChQGO GdCSHhY(B"s - (3GdMGJej, GdWGFj, GHf YQHj, eMjj GdOjf, eMeO Hf Ydj Hf eMeO Hf YQHj, J(B638(3g`s
(3ChdgG (B:s
(3HSe Gddg aGJM GdhLhO hGdMeO ddg eXgQ cd ehLhOs
(3BNQgG (B:s
(3dG Edg EdG CfJ SHMGfc Efj cfJ ef GdXGdejf hCfJ CQMe GdQGMejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 281s
(3eYLe GdeDdajf(B: 3 / 531s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs